Automatic Detection of Sunspots Size and Activity using Matlab - Kamel, Noor Alhuda; Selman, Ahmed Abdul-Razzaq (Iraqi Journal of Science, 2019)
A study is made about the size and dynamic activity of sunspot using automatically detecting Matlab code ''mySS .m'' written for this purpose which mainly finds a good estimate about Sunspot diameter (in km). Theory of the Sunspot size has been described using equations, where the growth and decay phases and the area of Sunspot could be calculated. Two types of images, namely H-alpha and HMI magnetograms, have been implemented. The results are divided into four main parts. The first part is sunspot size automatic detection by the Matlab program. The second part is numerical calculations of Sunspot growth and decay phases. The third part is the calculation of Sunspot area. The final part is to explain the Sunspot activity during the end of 24th solar cycle. The relationship between the number of Sunspot and the time evolution describe solar surface activity. Calculations made in this work focused on the period from 2010 till 2018. Results indicated that growth rate is found from the fitting velocity of Sunspots radius variation due to the time of Sunspots evolution. The Sunspots decayed in the period time (17-27 Aug 2011) and (14-25 Nov 2010) when using H-alpha images more than other years of the study, and the little variation in the size of the Sunspots happened in (03-14 Sep 2016) when using H-alpha images. Results of the third part showed Sunspots continued changing during the time of study. The explanation was that more spots appear at the beginning and the magnetic field is strong when the area of observed sunspots increased with time, and vice versa. Results of the fourth part showed that the Sun in 2018 was the least active in that period, and in 2014 it was at highest activity.